2017
DOI: 10.1007/s00264-017-3592-1
|View full text |Cite
|
Sign up to set email alerts
|

Blunt injuries related to equestrian sports: results from an international prospective trauma database analysis

Abstract: Young female riders are at risk from falling, horse-kicks, and crush-injuries. Older males in carriage-related accidents sustained the highest injury severity and mortality rate, and must specifically be targeted by future prevention initiatives. Level of evidence Descriptive Epidemiologic Study, Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 38 publications
3
16
1
Order By: Relevance
“…They had higher odds for serious outcomes in all tested parameters. We thus confirm recent observations of authors 1 12 14 who observed same tendencies in their datasets. This shows a contrast to other studies, which did not emphasise any effect of gender.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…They had higher odds for serious outcomes in all tested parameters. We thus confirm recent observations of authors 1 12 14 who observed same tendencies in their datasets. This shows a contrast to other studies, which did not emphasise any effect of gender.…”
Section: Discussionsupporting
confidence: 93%
“…Horseback riding is one of the most popular recreational activities in Europe, 1 and equine-related accidents increased in the past years. 2–4 The power of a horse can expose the rider to a potential high-energy trauma.…”
Section: Introductionmentioning
confidence: 99%
“…Fatalities from horse kick have been reported, most commonly resulting from head trauma (Kiuru et al, 2002; Jagodzinski and DeMuri, 2005; Ebert et al, 2012; Carmichael et al, 2014). Horse kick injuries make up approximately 8.1% to 30% of all horse-related injuries and can result in more severe injury than other horse-related mechanisms (Kiuru et al, 2002; Jagodzinski and DeMuri, 2005; Carmichael et al, 2014; Weber et al, 2017; Adler et al, 2019). As a majority of the literature on head trauma from horse kicks is retrospective in nature, there is somewhat limited evidence on the direct effect of a horse kick on the cranium and underlying brain.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that 86% of equine-related trauma occurred in female riders. Although this is not a dissimilar proportion of injuries relative to the number of female riders, Weber et al have in fact determined female riders to be at a higher risk of sustaining falls from height than their male counterparts [6]. In addition, Majeedkutty et al demonstrated a significant correlation between the female gender and the prevalence of horseback riding injuries [7].…”
Section: Discussionmentioning
confidence: 99%